AVALIAÇÃO DE ESTRESSE OXIDATIVO EM TRABALHADORES RURAIS ATRAVÉS DA MEDIDA DE GRUPOS SULFIDRÍLICOS - BANDEIRA, CAMILA D. S.; VIEIRA, CAROLINA P.; SANTOS, GREICE F. F. D.; BELLINASO, MARIA D. L.; GOETTEMS, PAULINE B. (Salão do Conhecimento, 2013)
Resumo